A Hydrogel Drink With High Fructose Content Generates Higher Exogenous Carbohydrate Oxidation and a Reduced Drop in Dental Biofilm pH Compared to Two Other, Commercially Available, Carbohydrate Sports Drinks - Pettersson, Stefan; Ahnoff, Martin; Edin, Fredrik; Lingström, Peter; Simark Mattsson, Charlotte; Andersson-Hall, Ulrika (Frontiers in Nutrition, 2020)
The purpose of this study was to evaluate the substrate oxidation of three commercially available, 14%-carbohydrate sports drinks with different compositions, osmolality and pH for their impact on dental exposure to low pH. In a cross-over, randomized double-blinded design, twelve endurance athletes (age 31.2±7.7 years, V̇O2max 65.6±5.0 mL∙kg-1) completed 180 min of cycling at 55% Wmax. During the first 100 min of cycling, athletes consumed amylopectin starch (AP), maltodextrin+sucrose (MD+SUC) or maltodextrin+fructose hydrogel (MD+FRU) drinks providing 95g carbohydrate·h-1, followed by water intake only at 120 and 160 min. Fuel use was determined using indirect calorimetry and stable-isotope techniques. Additionally, dental biofilm pH was measured using the microtouch method in a subsample of participants (n=6) during resting conditions before, and at different time intervals up to 45 min following a single bolus of drink. Mean CHOEXO during the second hour of exercise was significantly (P<0.05) different between all three drinks: MD+FRU (1.17±0.17g·min-1), MD+SUC (1.01±0.13g·min-1) and AP (0.84±0.11 g·min-1). At the end of exercise, mean CHOEXO and blood glucose concentrations (3.54±0.50, 4.07±0.67, and 4.28±0.47mmol·L-1, respectively) were significantly lower post MD+FRU consumption than post MD+SUC and AP consumption (P< 0.05). Biofilm acidogenicity at rest demonstrated a less pronounced pH fall for MD+FRU compared to the acidulant-containing MD+SUC and AP (P< 0.05). In conclusion, while total intake of MD+FRU showed signs of completed uptake before end of monitoring, this was less so for MD+SUC, and not at all the case for AP. Thus, this study showed that despite carbohydrates being encapsulated in a hydrogel, a higher CHOEXO was observed following MD+FRU drink ingestion compared to AP and MD+SUC consumption upon exposure to the acidic environment of the stomach. This finding may be related to the higher fructose content of the MD+FRU drink compared with the MD+SUC and AP drinks. Furthermore, a carbohydrate solution without added acidulants, which are commonly included in commercial sport drinks, may have less deleterious effects on oral health.